PENERAPAN MANAJEMEN KONFLIK DI SMK NEGERI 1 PALANGKA RAYA - Azarya Aprinata; Betris Betris; Restiana Restiana; Defri Triadi (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Conflict management plays a role in handling and resolving conflicts in organizations. Conflict management contains several types and models of resolution according to the type of conflict that occurs. The purpose of this research is to find out and explain the strategy of SMK Negeri 1 Palangka Raya in responding to and resolving conflict problems between leaders, employees and students, the types of conflicts that occur and the challenges in resolving them. This research method uses a qualitative descriptive approach with data collection techniques in the form of interviews. Data analysis techniques include collection, reduction, data presentation, and drawing conclusions. The research results show that conflicts originating from student behavior require a comprehensive approach involving counseling guidance, parental involvement, and career guidance in order to overcome underlying problems effectively.